Early infantile ceroid lipofuscinosis -- role of nuclear magnetic resonance in the diagnosis. - Reis, A M (2001)
The authors report a case of Infantile Neuronal Ceroid Lipofuscinosis and emphasize the role of MRI in the diagnosis and follow-up of the disease describing a severe progressive cerebral atrophy. Clinical findings and laboratory data were reviewed and the importance of palmitoyl-protein thiosterase activity is described.